A (in)sustentabilidade dos pronunciamentos nos tribunais quanto à impenhorabilidade da propriedade rural de subsistência nos pactos realizados entre os agricultores e os idólatras de Mamon. - Leal , Miron Biazus (2023)
This research investigates the unsustainability through the theory of douglass north of the enforcemet of the pronouncements of the STJ and STF as for the issue of the unseizability of the small subsistence farm and its unsustainable effects. The specific objectives are: Define the performance of the Judiciary in time; Identify the formative elements of the family farmer and his family; Seek the Elements that make up the unseizability of the subsistence rural property; Outline the financial agents and their role in transactions with family farmers in an allegorical parallel with the figure of Mammon; To verify whether the pronouncements of the STJ and STF are unsustainable and unconstitutional in cases of unenforceability of small subsistence property, through the institutional framework and law enforcement. In view of the peculiarity and importance of protecting the way of life in family farming through impenhorability, it is asked: The Enforcement of the pronouncements coming from the STJ and STF regarding the unenforceability of the small subsistence property, in the appeals and related cases Are the debts contracted by the peasants with the financial institutions sustainable? To answer this question, 6 distinct and interconnected chapters were developed, with the application of the methods: interpretive dialectic and legal hermeneutics, and use of research: qualitative and quantitative, through books, scientific journals, periodicals, documents and jurisprudence. The research concluded that the application and non-binding interpretation of the STJ newsletters, especially the 616/2018 added to the vagueness of the binding issue existing in the Supreme Court 591/2020, cause unsustainability in the pronouncements, transactions and negotiations carried out between the players, because it does not exist any penalties to the players and magistrates (executors) when the non-compliance with the judgments issued by those Courts.